2020
DOI: 10.51481/amc.v59i4.979
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the burden of herpes zoster disease in Costa Rica

Abstract: Background: Herpes zoster is a distressing illness that significantly reduces patients’ quality of life. However, Costa Rican data regarding the clinical burden of herpes zoster and associated health care resource utilization is limited. This study aimed to assess the zoster-associated burden evaluating pain, impact on quality of life and health care resource utilization in a Costa Rican sample.Methods: Herpes zoster patients recruited in Costa Rica at a private geriatric practice were enrolled at various time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…La carga clínica y económica del HZ se ha estudiado previamente en otras regiones de América Latina (21)(22)(23)(24)(25); sin embargo, hasta donde tenemos conocimiento, este es el primer informe sobre la carga del HZ en un contexto colombiano. En general, los hallazgos de este estudio prospectivo, observacional indican que la carga del HZ en Colombia es alta, afecta la calidad de vida, promueve la utilización de recursos y resulta en tasas elevadas de dolor posherpético, prodrómico y agudo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La carga clínica y económica del HZ se ha estudiado previamente en otras regiones de América Latina (21)(22)(23)(24)(25); sin embargo, hasta donde tenemos conocimiento, este es el primer informe sobre la carga del HZ en un contexto colombiano. En general, los hallazgos de este estudio prospectivo, observacional indican que la carga del HZ en Colombia es alta, afecta la calidad de vida, promueve la utilización de recursos y resulta en tasas elevadas de dolor posherpético, prodrómico y agudo.…”
Section: Discussionunclassified
“…Asimismo, y de acuerdo con la tendencia identificada en los estudios previos de la carga del HZ (22,25,(27)(28)(29)(30), los aumentos del dolor estuvieron acompañados de reducciones en la CV, según la medición mediante el EQ-5D. Las puntuaciones promedio y del peor "dolor del ZBPI en las últimas 24 horas" llegaron al máximo el día 7, en 5.2 y 6.4, respectivamente, y las puntuaciones más bajas de la VAS del EQ-5D, de 70.5 mm, se observaron en el mismo punto de evaluación.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…We found that the prevalence of certain immunocompromising conditions (e.g., SLE and HIV) and immunosuppressive therapy was higher in younger patients, which was consistent with this recognizable risk factor in this age group, whereas ageing itself (i.e., the natural age-related decline in immunity) was more relevant in older adults. 3,4,11,16 Over 60.00% of the patients were aged ≥ 50 years, with 42.98% ≥ 60 years of age; the majority (70.00%) were women. These demographic characteristics are similar to previous reports from Brazil 9,10 and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…These demographic characteristics are similar to previous reports from Brazil 9,10 and elsewhere. 3,4,11,16 Supplemental Figure 1 presents a plain-language summary of the context, outcomes, and relevance of this study for healthcare providers.…”
Section: Discussionmentioning
confidence: 99%